Amycolatopsis nivea sp. nov., isolated from a Yellow River sample. Issue 5 (6th April 2020) - Niu, Ming-Ming; Ming, Hong; Cheng, Li-Jiao; Zhao, Zhuo-Li; Ji, Wei-Li; Li, Meng; Yi, Bing-Fang; Xia, Ting-Ting; Nie, Guo-Xing
Abstract : A novel actinobacterium, designated strain CFH S0261 T, was isolated from a sediment sample of the Yellow River. The taxonomic position of the strain was investigated by using a polyphasic approach. Cells of strain CFH S0261 T were Gram-reaction-positive, aerobic, non-motile. Growth occurs at 15–37 °C, pH 6.0–8.0 and with 0–9.0 % (w/v) NaCl. Phylogenetic analysis based on the 16S rRNA gene sequence revealed that strain CFH S0261 T was a member of the genus Amycolatopsis . The 16S rRNA gene sequence similarity indicated that strain CFH S0261 T is most closely related to the type strains of Amycolatopsis niigatensis LC11 T (98.95 %), Amycolatopsis echigonensis LC2 T (98.81 %) and Amycolatopsis albidoflavus IMSNU 22139 T (98.73 %). The whole-genome of CFH S0261 T showed a G+C content of 69.5 mol%. The ANI values and in silico DDH values between CFH S0261 T and the other species of the genus Amycolatopsis were found to be low (ANIb <90.61 % and DDH <53.40 %). The cell wall diamino acid in the peptidoglycan of strain CFH S0261 T was meso -diaminopimelic acid and the whole-cell hydrolysate comprised arabinose, galactose, glucose, rhamnose and ribose. The predominant menaquinone was MK-9(H4 ). The major cellular fatty acids were C16 : 0, iso-C15 : 0 and iso-C16 : 0 . The polar lipid profile contained diphosphatidylglycerol, phosphatidylglycerol, phosphatidylethanolamine, phosphatidylinositol, phosphatidylinositol mannosides and four unidentified glycolipids. On the basis of phenotypic, genotypic and phylogenetic data, strain CFH S0261 T represents a novel species of the genus Amycolatopsis, for which the name Amycolatopsis nivea sp. nov. is proposed. The type strain is CFH S0261 T (=KCTC 39515 T =CCTCC AA 2014028 T ).